A Review on Herbal Drug Therapy for Diabetes Mellitus (World Journal of Current Medical and Pharmaceutical Research, 2019)
This review focuses on the study of herbal drugs used in Diabetes mellitus treatment. Diabetes mellitus becomes a common metabolic disorder that poses a serious threat to the world's public health. Approximately 60 percent of the world's population use traditional medicines derived from medicinal plants. Due to lower side effects and low cost, herbal formulations are favored. Synonymous with herbal medicine, phytomedicine or botanical medicine, plants are used for medicinal purposes. Herbal selection may depend on a number of factors, including the stage of diabetes progression, the types of comorbidities that patients have, availability, affordability, and herbal safety profile. A list is compiled of medicinal plants with proven antidiabetic and related beneficial effects and herbal medicines used in diabetes treatment.